UNMET NEED FOR FAMILY PLANNING IN GUNUNGPATI DISTRICT: 2013-2022 - Salsabila, Annisa Putri (HIGEIA (Journal of Public Health Research and Development), 2023)
Abstract Unmet need for family planning (FP) is a significant public health problem that cause 20% of obstetric deaths. Unmet need rate in Central Java according to the data from Central Statistics Agency reached 15.9% and Semarang City reached 8.94% which is still far from the MDGs target of 5%. This study aims to review the incidence of unmet need for family planning in Gunungpati district which is expected can be use as a consideration for policy making. Research design of this study is an analytic research with ecological approach that examines family data in Gunungpati district. The incidence of unmet need in Gunungpati district from 2013 to 2022 decreased significantly from 2013 to 2019, then increased in 2022. The highest number of cases occurred in 2013, while the lowest cases occurred in 2019 with the highest number of cases found consecutively in Sukorejo, Sekaran, and Sumurrejo sub-districts. There is a significant correlation between age of reproductive aged couples, number of births, educational status of the family head, gender of the family head, and employment status of the family head with incidence of unmet need for family planning in the spacing and limit categories in Gunungpati district. Research on risk factors for unmet need for family planning at individual level can be carried out to increase the input for controlling unmet need for family planning. Keywords: Unmet need, Family Planning, Spacing, Limit Abstrak Unmet need Keluarga Berencana (KB) merupakan masalah kesehatan masyarakat yang signifikan dan menyebabkan 20% kematian obstetrik. Angka unmet need di Jawa Tengah menurut data Badan Pusat Statistik mencapai angka 15,9% dan di Kota Semarang mencapai 8,94% yang masih jauh dari target MDGs yakni 5%. Penelitian ini bertujuan untuk meninjau kejadian unmet need KB di Kecamatan Gunungpati yang diharapkan dapat dimanfaatkan sebagai pertimbangan pengambilan kebijakan. Desain penelitian ini adalah penelitian analitik dengan pendekatan ekologi yang mengkaji data keluarga di Kecamatan Gunungpati. Kejadian unmet need di Kecamatan Gunungpati dari tahun 2013 hingga 2022 menurun secara signifikan dari tahun 2013 hingga 2019, kemudian meningkat pada tahun 2022. Jumlah kasus tertinggi terjadi pada tahun 2013, sedangkan kasus terendah terjadi pada tahun 2019 dengan jumlah kasus tertinggi ditemukan secara berturut-turut pada Kecamatan Sukorejo, Sekaran, dan Sumurrejo. Terdapat korelasi yang signifikan antara Usia PUS, Jumlah Kelahiran, Status Pendidikan Kepala Keluarga, Jenis Kelamin Kepala Keluarga, dan Status Pekerjaan Kepala Keluarga dengan kejadian unmet need KB pada kategori IAD maupun TIAL di kecamatan Gunungpati. Penelitian mengenai faktor risiko unmet need KB di tingkat individu dapat dilakukan guna meningkatkan input pengendalian unmet need KB. Kata kunci: Unmet need, KB, IAD,TIAL